A review of free fatty acid determination methods for palm cooking oil - Noor Azlinna, Azizan; Nurulain Nadhirah, Shaipizaman; Muhammad Sharfi, Najib; Mohd Rashidi, Salim; Hadi, Manap (IOP Publishing, 2021)
Palm oil quality is depending on free fatty acids (FFA) content in palm oil. High content of FFA in palm oil leads to various health issues and affect the quality of palm oil. Based on quality standards specification set by Malaysia Palm Oil Board (MPOB), the amount of free fatty acids content for crude palm oil (CPO) is maximum 5% and should be less 0.1% in Refined Bleached Deodorized Oil (RBDO). There are many researches have been carried out to determine the level of FFA. However, they are using different type of cooking oil. A few researches are also reported regarding the palm cooking oil but they are using different method such as titration, spectroscopic, gas chromatography, reflection method and other type of detectors. This paper reviews all methods reported to determine free fatty acids in palm oil.